Collaboration role in semantic integration for electronic marketplace. (29th November 2010) - Guo, Jingzhi
Semantic integration is important in constructing electronic marketplaces (e-marketplaces). Although many previous researches have been done, the task of semantic integration and the mechanism of maintaining semantic consistency are still not well known. This paper proposes a Collaboration-Role-Based Semantic Integration Mechanism (CRB-SIM). It promotes collaboration as a key means of resolving semantic conflicts in concepts creation and editing, via a set of service-oriented collaboration roles. This proposal has contributed to the semantic integration research a novel approach with the features of the role-based and service-oriented semantic consistency maintenance of heterogeneous concepts. The applicability of proposed mechanism is exemplified by two application prototypes.